A Strategy for Management of Sustainable Water Supply System in Rural Areas - Rusdiana Setyaningtyas Wachid (ITB Journal Publisher, LPPM ITB, 2022)
The sustainability of rural drinking water supply systems (SPAM) is an important development issue in Indonesia related to the low access to clean and healthy water in rural areas. The low level of drinking water service in rural areas is inseparable from the failure of drinking water development which is caused by the absence of an optimal rural drinking water supply system. As happened in post-Pamsimas villages in Jember Regency. This condition is the background for researchers in conducting studies to find out what factors affect the sustainability of the use of SPAM facilities and infrastructure that are built, especially from the Pamsimas program based on the fulfillment of the KPI (Key Performance Indicator) target, namely KPI 3 related to the management of